Teaching building performance simulation: Considerations on methodologies and course levels. Issue 4 (October 2019) - Hernandez Neto, Alberto
This paper presents considerations on three aspects of teaching building simulation: course content, students' background, and teaching methodology. Based on the literature review, an overview of different strategies and courses formats for teaching building performance simulation is presented. Combining the information gathered in the literature review, the feedback from the students in a short course and an online survey with simulation experts, these aspects are analyzed, and some suggestions and actions are presented. Among the several methodologies presented in the literature review, the project or problem-based methodology provides the best results for an effective learning. Also, a proposal for course format is presented taking into account different students' backgrounds (novice, intermediate, advanced, and expert).